Trajectory big data:data,applications and techniques - Jia-jie XU; Kai ZHENG; Ming-min CHI; Yang-yong ZHU; Xiao-hui YU; Xiao-fang ZHOU (Tongxin xuebao)
The fast development of mobile internet has given rise to an extremely large volume of moving objects trajectory data.These data not only reflect the spatio-temporal mobility of individuals and groups,but may also contain the behavior information of people,vehicles animals,and other objects of interest.They are invaluable for route planning,urban planning and vehicle monitoring,etc.,and tremendous efforts have been made to support effective trajectory data management,including trajectory data pre-processing,which handles issues such as high redundancy,low precision and inconsistency of sampling; trajectory database technologies,concerning the efficient and effective storage of trajectory data and query processing; trajectory data warehousing,which supports the analytics on large-scale trajectory data;knowledge discovery,by which useful patterns can be extracted from trajectory data.A survey of trajectory big data analytics from three different aspects:data,applications and techniques is provided.